2011
DOI: 10.1038/ki.2010.463
|View full text |Cite
|
Sign up to set email alerts
|

Comparative profile of commercially available urinary biomarkers in preclinical drug-induced kidney injury and recovery in rats

Abstract: We designed a study to provide reversibility and comparative injury data for several candidate urinary biomarkers of kidney injury in the United States Food and Drug Administration biomarker qualification process. The nephrotoxin gentamicin was given to rats once on each of three days and the animals were killed during dosing or over the following 42 days. Between days one and three, all biomarkers except albumin were elevated, peaked at day 7, and returned to control levels by day 10 (μ- and α-glutathione S-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 36 publications
5
60
0
1
Order By: Relevance
“…In our study, marked increases NGAL was observed in urine, and necrosis and swelling of proximal epithelium and regeneration of proximal and distal epithelium were noted in the dog given the high dose of gentamicin. Although immunohistochemistry of frozen and paraffin section in the dog kidney using commercially available anti-NGAL antibodies was failed to identify NGAL expression and its distribution in this study, it was reported that NGAL mRNA was highly upregulated after kidney injury such as renal ischemia-reperfusion, and cisplatin or gentamicin nephropathy in rodents (Mishra, 2003;Rouse et al, 2011). In the high dose treatment of this study, reabsorption of NGAL in the proximal epithelium was considered to be the main reason for the increase in urinary NGAL due to severe proximal tubular lesions, and elevation of NGAL synthesis and/or secretion in injured tubular epithelium may also contribute to the changes.…”
Section: Discussionmentioning
confidence: 80%
“…In our study, marked increases NGAL was observed in urine, and necrosis and swelling of proximal epithelium and regeneration of proximal and distal epithelium were noted in the dog given the high dose of gentamicin. Although immunohistochemistry of frozen and paraffin section in the dog kidney using commercially available anti-NGAL antibodies was failed to identify NGAL expression and its distribution in this study, it was reported that NGAL mRNA was highly upregulated after kidney injury such as renal ischemia-reperfusion, and cisplatin or gentamicin nephropathy in rodents (Mishra, 2003;Rouse et al, 2011). In the high dose treatment of this study, reabsorption of NGAL in the proximal epithelium was considered to be the main reason for the increase in urinary NGAL due to severe proximal tubular lesions, and elevation of NGAL synthesis and/or secretion in injured tubular epithelium may also contribute to the changes.…”
Section: Discussionmentioning
confidence: 80%
“…Potential biomarkers also have to be considered in the type of evaluation offered. (50,51) Kidney injury assessments may be made via measurements of kidney function, oxidative stress, cellular and structural injury, immune responses, and fibrosis. Clearly, a panel of biomarkers is attractive in that it is able to provide a more holistic assessment of kidney injury, be it AKI or CKD; however, the research methodology, analysis, interpretation, and clinical application will be challenging.…”
Section: Disease Acuity and Type Of Biomarkermentioning
confidence: 99%
“…Both of these proteins have compelling preclinical data as early indicators of AKI and appear promising in initial translation experiments in humans (9)(10)(11)(12)(13). In addition, KIM-1 was recently approved by the US Food and Drug Administration as an AKI biomarker for preclinical drug development (14,15) and L-FABP is approved as a diagnostic test for human AKI in Japan. This study represents the first large-scale validation of these two biomarkers and offers comparisons with other novel biomarkers of AKI.…”
Section: Introductionmentioning
confidence: 99%